ANALISIS SENTIMEN HATESPEECH PADA TWITTER DENGAN METODE NAÏVE BAYES CLASSIFIER DAN SUPPORT VECTOR MACHINE (Dinamika Informatika, 2016)
Abstract— Today, social media, especially Twitter have enormous influence to the success or ruin the image of a person. Many movements are carried out in social media, especially Twitter, all of which can influence its success. There is a movement that aims good there is also a movement with malicious purposes, namely hatred to others. Usually the movement on Twitter was done using the hashtag (#), the latest movement there tagar Hatespeech (#HateSpeech), viewed from the name is already clear that hate speech. This study analyzes the hashtag proficiency level, all justified by the hashtag was the sentiment of hate. The classification process in this study using the method of classification Naive Bayes classifier (NBC) and Support Vector Machine (SVM) with the data preprocessing using tokenisasi, cleansing and filtering. The data used are in Indonesian tweet with the hashtag HateSpeech (#HateSpeech), with the number of datasets as much as 522 tweets were distributed evenly into two sentiments HateSpeech and GoodSpeech. The highest accuracy of results obtained when using the method of classification Support Vector Machine (SVM) with tokenisasi unigram, stopword list Indonesian and emoticons, with the average value reached 66.6% accuracy, precision value of 67.1%, 66.7% recall value TP value rate of 66.7% and 75.8% rate the value TN. Keywords—Sentiment Analysis; HateSpeech; Twitter; Data Mining; Naive Bayes classifier (NBC); Support Vector Machine (SVM); Sekarang ini, media sosial khususnya Twitter mempunyai pengaruh yang sangat besar bagi kesuksesan ataupun kehancuran citra seseorang. Banyak gerakan-gerakan yang dilakukan dalam media sosial khususnya Twitter yang semuanya sukses mampu mempengaruhi penggunanya. Ada gerakan yang bertujuan baik ada juga gerakan dengan tujuan jahat yaitu menebar kebencian kepada orang lain. Biasanya gerakan di Twitter itu dilakukan dengan menggunakan tagar (#), Gerakan terbaru ada tagar Hatespeech (#HateSpeech), dilihat dari namanya sudah jelas yaitu ucapan kebencian. Penelitian ini menganalisis tagar tesebut, benarkan semua yang diberi tagar itu sentimennya kebencian. Proses klasifikasi pada penelitian ini menggunakan metode klasifikasi Naïve Bayes Classifier (NBC) dan Support Vector Machine (SVM) dengan preprocessing data menggunakan tokenisasi, cleansing dan filtering. Data yang digunakan adalah tweet dalam bahasa Indonesia dengan tagar HateSpeech (#HateSpeech), dengan jumlah dataset sebanyak 522 tweet yang didistribusikan secara merata menjadi dua sentimen HateSpeech dan GoodSpeech. Hasil akurasi tertinggi didapatkan saat menggunakan metode klasifikasi Support Vector Machine (SVM) dengan tokenisasi unigram, stopword list Bahasa Indonesia dan emoticons, dengan nilai rata-rata akurasi mencapai 66,6%, nilai presisi 67,1%, nilai recall 66,7% nilai TP rate 66,7% dan nilai TN rate 75,8%. Kata kunci – Analisis Sentimen; Sentiment Analysis; HateSpeech; Twitter; Data Mining; Naive Bayes Classifier (NBC); Support Vector Machine (SVM);.